MEANING SHIFTS IN THE TRANSLATION OF FIGURATIVE EXPRESSIONS IN NAJIB AL-KILANI’S AMÂLIQATU ASY-SIMÂL - Silmi Malina Binta; Khairon Nahdiyyin; Muhammad Fadhil Syahridho (Arabic Literature Department, 2023)
The novel Amâliqatu asy-Simâl by Najib al-Kilani narrates the true story of the civil war in Nigeria during British colonization. The linguistic and cultural differences that form the story's background necessitate a specific translation method for translating figurative expressions in the novel. This article examines the types of figurative expressions in the novel and the shifts in meaning that occur in translation. The method used in this research is a qualitative descriptive method with an al-bayan science approach and the theory of meaning shifts. The results show 17 expressions containing majaz, including ten forms of 'isti'arah, three majaz mursal, and four kinayah. The translation achieves shifts in meaning through adding, replacing word class, and substituting due to semantic proximity.